Study on quantifying carbon in the soil of mangrove plantation in Nam Hung community, Tien Hai district, Thai Binh province - Hong Hanh, Nguyen Thi (Academia Journal of Biology, 2014)
The study is focused on evaluating the carbon accumulation ability of mangroves, contributing to reducing the greenhouse gases emission, responsing the climate change, supporting the international negotiations in implementation of the reducing greenhouse gases emission programs such as REDD, REDD+ as well. Our research of carbon quantification of soil mangrove plantation was carried out in Nam Hung community, Tien Hai district, Thai Binh province. The results showed that planted forests impact on the carbon accumulation underground which is upon the growing time, trends to increasing following the forest growth. In this study, underground carbon accumulation reached the highest value with 85.80 tons/ha in R4T, followed with 78.68 tons/ha in R3T and 72.86 tons/ha. In the areas without plants, underground carbon accumulation was 49.67 tons/ha, lower than in which forests planted. Sonneratia caseolaris forests have ability of large amount of carbon accumulation, contributing to reduction of greenhouse gases emissions, improving climate change adaptation. The ability of highly carbon accumulation of mangrove forests plays important role for the implementation of REDD, REDD+ in Vietnam.